Community structure of nekton in the upstream of Wampu Watershed, North Sumatra, Indonesia - DESRITA DESRITA; AHMAD MUHTADI; ISTEN SWENO TAMBA; JENI ARIYANTI; RINA DRITA SIBAGARIANG (Society for Indonesian Biodiversity, 2018)
Desrita, Muhtadi A, Tamba IS, Ariyanti J, Sibagariang RD. 2018. Community structure of nekton in the upstream of Wampu Watershed, North Sumatra, Indonesia. Biodiversitas 19: 1366-1374. River is a habitat for many aquatic organisms. Water quality is the main river characteristic that strongly influences distribution pattern, biodiversity, and abundance of aquatic organisms. Nekton is aquatic organism that swims and moves actively on their desire, for example, fish, shrimp, amphibian and also big aquatic insects. The purpose of this research was to know the habitat condition and biodiversity of nekton in the upstream of Wampu watershed. The habitat condition was measured by examining the temperature, visibility, flow velocity, depth of waters, dissolved oxygen, pH, kind of substrate, the width of the river, body width of river and rate of flow of the river. The type of nekton was determined by catching the nekton using a backpack of electrofishing unit with an electric flow of 12 Volt and 9 Ampere. The upstream habitat condition of Wampu watershed was characterized by big stone, pebble, sandy type of substrate with moderate to strong current flow, and the clear aquatic. Physical and chemical parameters in upstream of Wampu watershed were still sustainable and appropriate as habitat for fish and shrimp. The result of this research showed a variety of nekton collected, comprised of 27 species of fish, five species of shrimp of inland water. Two species of fish from Tor genera, i.e., T. soro and T. tambroides were also found in this study. The highest diversity (H´) in this research site was the Bahorok River (2.12), followed by Landak River (1.93) at the second, and the lowest was Berkail River with only about 1.50 diversity index.